Pregnancy in a Renal Transplant Recipient with HIV-1 Infection: A Case Report. Issue 3 (April 2016) - Agüero, Fernando; Cofan, Frederic; Fortuny, Claudia; Lopez, Marta; Manzardo, Christian; Lonca, Montserrat; Oppenheimer, Frederic; Moreno, Asuncion; Campistol, Josep M; Miro, Jose M
We report the first case of a pregnancy in a renal transplant recipient with HIV infection. She underwent renal transplantation in 2005 and became pregnant in 2009. The patient underwent vaginal delivery and a healthy full-term, female baby was born. Almost 6 years after delivery, both mother and child were doing well. The management of concurrent renal transplantation, HIV infection and pregnancy was extremely challenging. Women with HIV infection who have undergone renal transplantation should be accurately informed of the potential health risks for them and their offspring. Multidisciplinary teams are mandatory in order to properly manage these patients.